The effect of complex decongestive therapy on spatio-temporal parameters and balance in women with breast cancer-related upper extremity unilateral lymphedema - Bilek, Furkan; Deniz, Gulnihal; Gulkesen, Arif (Elsevier Sci Ltd, 2023)
Background: The aim of this study was to investigate the effect of complex decongestive therapy on spatio-temporal parameters and balance in individuals with breast cancer-related upper extremity unilateral lymphedema.Methods: The study was designed as a prospective, cross-sectional study. Thirty sessions of complex decongestive therapy were applied. Participants' pre-and post-treatment spatio-temporal parameters and balance parameters were evaluated with the Win Track platform. In addition, the Timed Up and Go test was used to evaluate the dynamic balance. Plethysmography, a water displacement method, was used to measure upper extremity volume.Findings: Significant improvement was observed in limb volume asymmetry after complex decongestive therapy. While the stride length of the affected side was 409.93 mm before the treatment, it increased to 500.93 mm after the treatment, and a significant increase was observed (p = 001). Significant improvements were found in the other spatio-temporal parameters of the participants. Compared to the pre-treatment, a significant decrease was detected in the average cadence value, Timed Up and Go value, double stance time, and maximum plantar pressure point of the participants. Significant improvements were found in the participants' balance.Interpretation: Complex decongestive therapy applied to individuals with unilateral upper extremity lymphedema provides significant improvement in both spatio-temporal and balance parameters. However, we recommend complex decongestive therapy as an effective and safe treatment to reduce the volume of lymphedema. Patients with unilateral lymphedema that may cause postural asymmetry should be informed about balance and gait disturbance and should be encouraged to receive lymphedema treatment as soon as possible.
Keywords: Gait; Postural balance; Rehabilitation; Spatio-temporal parameters; Unilateral lymphedema; Complex decongestive therapy